Synthesis, Spectroscopic Characterization and Antibacterial Activity of Organotin(IV) Complexes Containing Hydrazone Ligand: X-ray Single Crystal Structure of [n-Bu2Sn(H2PAI).H2O] - Affan, M. A.; Fasihuddin, B. A.; Liew, Y. Z.; Foo, S. W.; Ismail, J. (Journal of Scientific Research, 2009)
Five new organotin(IV) complexes with pyruvic acid isonicotinoyl hydrazone [H4PAI (1)] of the general formula [Me2Sn(H2PAI)] (2), [R2Sn(H2PAI).H2O] [R=n-Bu, (3) or Ph, (4)], [RSnCl(H2PAI).H2O] [R=Me (5) or Ph (6)] have been synthesized in the presence of base in absolute methanol in 1:2:1 mole ratio (metal:base:ligand). All organotin(IV) complexes are characterized by elemental analyses, molar conductance values, UV-Visible, IR and 1H NMR spectral studies. The crystal structure of organotin(IV) complex (3) has also been determined by X-ray crystallography diffraction analyses. Complex [n-Bu2Sn(H2PAI).H2O] (3) is orthorhombic with space group P2(1)/c with a=27.517(5), b=9.6574(18), c=15.742(3) Å, α=90°, β=90°, γ=90°, V=4183.4(13) Å3, Z=8 and Dcalc=1.448 mg m-3. The complex [n-Bu2Sn(H2PAI).H2O] (3) shows a distorted octahedral geometry with coordination for the central tin(IV) atom and exhibits two monomeric structures in one unit cell. In the complex (3), the pyruvic acid isonicotinoyl hydrazone ligand is coordinated to the tin(IV) as dinegative tridentate chelating agent via the carboxylic-O, enolic-O and imine-N atoms. Hydrazone ligand (1) and its organotin(IV) complexes have also been screened for their antimicrobial activities and found to be relatively active. Keywords: Organotin(IV) complexes; Hydrazone ligand; Spectral studies; Crystal structure; Antibacterial activity. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1775